2023
DOI: 10.1002/bse.3517
|View full text |Cite
|
Sign up to set email alerts
|

The role of CEO regulatory focus in increasing or reducing corporate carbon emissions

Andreas Wagner,
Denise Fischer‐Kreer

Abstract: This article contributes to the emerging stream of corporate carbon emission research, which zooms in on CEOs' responsibility in organizations' strategic decision‐making. This investigation offers new knowledge of how a CEO's regulatory focus can shape whether firms reduce their carbon footprints. Building on regulatory focus theory, this study proposes how the two distinct motivational dispositions (i.e., promotion or prevention focus) of a CEO relate to corporate carbon emissions. We empirically analyzed S&a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…Prior evidence has demonstrated that different regulatory foci of CEOs have different firm-level responses to various types of strategic decisions, including firm acquisitions (Gamache et al 2015), strategic change (Huang and Zheng 2022), internationalization (Biru et al 2023), and carbon emission performance (Wagner and Fischer-Kreer 2024). Surprisingly, less attention has been paid to exploring the implications of CEO regulatory focus for corporate ethical conduct (e.g., CSR).…”
Section: Literature and Hypothesesmentioning
confidence: 99%
“…Prior evidence has demonstrated that different regulatory foci of CEOs have different firm-level responses to various types of strategic decisions, including firm acquisitions (Gamache et al 2015), strategic change (Huang and Zheng 2022), internationalization (Biru et al 2023), and carbon emission performance (Wagner and Fischer-Kreer 2024). Surprisingly, less attention has been paid to exploring the implications of CEO regulatory focus for corporate ethical conduct (e.g., CSR).…”
Section: Literature and Hypothesesmentioning
confidence: 99%
“…In terms of managerial characteristics, Jiang et al (2022) find that enhancing executives' lowcarbon cognition promotes low-carbon practices in high-tech and manufacturing firms. Wagner and Fischer-Kreer (2023) suggest that the promotion focus of a CEO increases corporate carbon emissions, but the prevention focus of a CEO reduces corporate carbon emissions. Additionally, several studies have investigated the impact of environmental information disclosure or internal carbon pricing on corporate carbon performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Firms are the major carbon emitters and thus are expected to take the responsibility to reduce carbon emissions. Against such background, the existing literature has explored the determinants of corporate carbon performance, such as board characteristics (Cahyono et al, 2023;Haque, 2017;Moussa et al, 2020), managerial characteristics (Jiang et al, 2022;Wagner & Fischer-Kreer, 2023), environmental information disclosure (Qian & Schaltegger, 2017), and internal carbon pricing (Zhu et al, 2022). Meanwhile, the government is the leader and manager of low-carbon economy, and its guiding role in regulating firms' low-carbon development practices cannot be overlooked.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By 2023, more than 130 countries around the world have made carbon-neutral commitments and implemented a series of policies and regulations to promote low-carbon production [3][4][5][6]. As the main source of energy consumption and carbon emission, enterprises play a crucial role in the implementation of emission reduction policies [7]. However, in reality, due to the lack of governmental guidance, the number of enterprises taking the initiative to reduce carbon emissions is small, and many of them have excessive carbon emissions [8].…”
Section: Introductionmentioning
confidence: 99%